Estimation of reindeer lichen biomass by image analysis - Jansson, Tomas (SLU/Dept. of Forest Ecology and Management, 2012)
During consultation procedures between forest owners and the Sámi, data on, e.g., reindeer lichen biomass on the current site is needed. Hitherto, the existing methods of measuring lichen cover and biomass has been either objective methods such as the Point Intercept method, which is time consuming, or some sort of subjective visual estimation, which is faster but less accurate. However, both these methods are sensitive to different observers and/or to different inventories. This paper addresses the further development and evaluation of a photographical inventory method that uses colour distribution in images to estimate lichen biomass. During the autumn of 2011 six different locations, with different grazing pressure and lichen cover, in Norrbotten county were inventoried using both the Point Intercept method and the photographical method, complemented with collection of biomass samples. The sample images were analyzed with respect to lichen and background areas (cover) using WinCAM™. Statistical analyses were used to create equations for estimation of lichen biomass from lichen cover, as well as to compare photographically estimated lichen cover and lichen cover from the Point Intercept method. Results shows that it is possible to estimate lichen biomass from lichen cover analyzed via image analysis. Results also indicate that different equations should be used for different sites depending degree of lichen cover and ground vegetation.